The impact of pelvic floor electrical stimulation on vaginal microbiota and immunity - Zhang, Yakun; Yang, He; Zhang, Chi; Lin, Li; Yang, Wenlan; Xiong, Guangwu; Gao, Guolan (Frontiers in Cellular and Infection Microbiology, 2022)
Pelvic floor electrical stimulation (ES) is an effective treatment for pelvic floor dysfunction. However, the impact of ES on vaginal microbiota and local inflammatory response is yet poorly understood. Therefore, we designed a longitudinal study to investigate the impact of ES on vaginal microbiota and cytokines. A total of 170 participants were recruited into the study at Peking University International Hospital, Beijing, China, from December 2021 to April 2022. They were divided into two groups concerning the follow-up: long-term cohort (n = 147) following up to seven treatment sessions and short-term cohort (n = 23) following up to 7 h after a 30-min treatment. Paired vaginal discharge samples were collected from 134 individuals. Vaginal microbiota was characterized by 16S rRNA sequencing, and local cytokines concentrations were detected by the cytometric bead array method. A significant increase in the relative abundance of Lactobacillus spp. was observed after ES treatment (P < 0.001). In addition, L. crispatus (P = 0.012) and L. gasseri (P = 0.011) also increased significantly. Reduced microbial diversity was observed in the vaginal microbiota after the treatment. In the long-term cohort, a significant downregulation of IFN-γ, IL-2, IL-4, IL-10, IL-17A, and TNF-α was compared with baseline. However, the short-term cohort presented with an elevated IL-6 level at 7 h after the treatment. In conclusion, this study suggested that transvaginal electrical stimulation might help to restore and maintain a healthy vaginal microbiota dominated by Lactobacillus, reducing the risk of vaginal inflammation.